Efektifitas Penggunaan EHR (Elektronik Health Record) Terhadap Efektifitas Waktu dan Perawatan: Literatur Review - Rahayu, Candra Dewi; Raharyani, Anisa Ell (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2017)
Background and Objectives: Experts consider information technology as the key to improving effectiveness, efficiency and quality in healthcare services. Documentation is a series of activities starting from the assessment, diagnosis, intervention, implementation and evaluation recorded either in the form of electronic or manual and can be responsibility.The objective of the review literature is to examine the effectiveness of the time of use of electronic documentation in the provision of nursing care. Methodology: Literature review is done by collecting the results of scientific publications in 2010-2017. Search by boleon method, full text, pdf, medeline. Further data are reviewed with CASP (Critical Appraisal Skill Program) tools and extracted then grouped for discussion and conclusion. Results:5 related studies of electronic documentation the criteria of researchers. The result of the review shows that the time used to perform electronic documentation is 9.2 minutes p-valeu 0.001 while the manual documentation is 7.5 minutes p-value 0.001. Involvement in documentation filling increased 10% p value <0.05 with the effectiveness of care time p = 0.001. Other results also show that the use of electronic documentation shows the length of stay decreased in patients in the Emergency Unit with a value of p = 0.01. The effectiveness of the time of the implementation of the documentation of care is influenced by the ability of human resources in performing electronic documentation. Conclusion: There is a need to develop the use of electronic documentation in health care system. Many interventions are needed from different perspectives to improve documentation and nursing care. Keywords: electronic documentation, time effectiveness of documentation, review literature